PENGGUNAAN POLIMER CMC-SISTEIN SEBAGAI FILM BUKAL SALBUTAMOL SULFAT - , Teguh Widodo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Buccal delivery system could be used as an alternative conventional delivery system since it may avoid first-pass metabolism and eliminate pre-systemic gastrointestinal tract. Salbutamol sulphate was selective Î²2 adrenoreceptor agonist compound used to treat bronchospasm and bronchoconstriction in asthma patients. The main obstacle of drug buccal delivery system was the relative weak ability of the mucoadhesive polymers, therefore the delivery system at specified location was insufficient. To improve the mucoadhesive nature, thiolated polymers or thiomers mucoadhesive that bind covalently to mucin was used. Conjugation between CMCNa and cysteine, carboxylate group on the polymer chain are activated by adding 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride or EDAC that serve as a catalyst. The aim of this study is to observe the effect of the EDAC concentration to the formation of polymer CMC-cysteine. Moreover, the polymer CMC-cysteine as buccal film application for salbutamol sulphate was well identified. The result showed CMC-cysteine formed a fibrous white solid, odorless and tasteless. The greater of EDAC concentration, the greater of cysteine conjugated to the polymer. The increasing of EDAC concentration (0, 20 and 40 mM) give the thiol content 29,17 Â± 4,16